Business environment : for BBA 3rd semester - Joshi, Rosy (Kalyani Publisher, 2013)
Business environment : for BBA 3rd semester / Joshi, Rosy. -- Kolkata: Kalyani Publisher, 2013 650 J84e4 4th ed. No. of Copies : 1